Influence of Different Educational Syllabus on Occurrence of Bruxism In 4 To 9 Years Old Children in Chennai - GURUNATHAN, DEEPA; MS, NIVEDHITHA; MOSES, JOYSON; RAMAKRISHNAN, MAHESH (The journal of contemporary issues in business and government, 2020)
Introduction: Bruxism is habitual involuntary grinding or clenching of teeth that is seen in both children and adults. Diurnal or nocturnal para-functional habit has also been called bruxism. The etiology of bruxism has remained controversial and some investigators believe that psychological factors may play a major role in promoting and perpetuating this habit. Aim of this study is to identify how educational system affects bruxism Materials and methods: 250 students of different educational syllabi were randomly chosen and examined. Questionnaire was given to their respective parents to the bruxism in children Result: Out of 250 children, 147 were studying in state government boards of education, 91 children studying in CBSE, and 12 children studying in montessori system. 60 out of 91 children studying CBSE, and 4 out of 12 children studying montessori system give a history of bruxism. Conclusion: Children studying in CBSE and Montessori had less number of bruxers compared to those children in state board curriculum.